A step in the right direction: the effect of context, strain and sex on paw preference in mice. (April 2021) - Stieger, Binia; Melotti, Luca; Quante, Sophia M.; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene
Abstract : Behavioural lateralization is a widespread phenomenon in the animal kingdom and can be an indicator of brain asymmetries in structure or function. It is often assessed using only one measure within the same study. Additionally, this measure is usually obtained in artificial situations, where the subjects undergo tasks requiring learning and forced performance of a specific action. Combining different measures of lateralization seems to be particularly promising, as artificially tested and spontaneously displayed behaviours may cover different aspects of behavioural lateralization. Therefore, the aim of the present study was to provide a comprehensive characterization of behavioural lateralization, using the laboratory mouse, Mus musculus f. domestica, as a model system. We examined lateralization using four behavioural measures, namely food reaching in an artificial test situation (the reference, most established, test) and three spontaneous behaviours (grid climbing, self-grooming and barrier crossing). We investigated their temporal consistency, assessed the association of the three spontaneous behaviours with the established food-reaching test and explored possible influences of genetic background and sex. We found differences in the distributions of lateralization across these behaviours, with fewer mice showing laterality in spontaneous behaviours. All behaviours showed high temporal consistency for the direction of laterality, while only food reaching did so for the strength of laterality. Furthermore, laterality of the spontaneous behaviours was unrelated to laterality of the food-reaching test. Lastly, strain affected behavioural lateralization, with C57BL/6J mice being more strongly lateralized than CD-1 mice for some behaviours, while sex did not affect it. Therefore, we conclude that behavioural lateralization is affected not only by genetic background, but also by the complexity of a given task. To obtain a comprehensive picture of behavioural lateralization, several measures from different contexts thus need to be included in a single study. Highlights: Behavioural laterality is often assessed via single measures in artificial settings. We combine different behavioural measures to assess laterality in mice. All observed behaviours are lateralized to a certain degree. Genetic background, but not sex, affects the strength of behavioural lateralization. Task complexity may affect behavioural differences in laterality.